2016
DOI: 10.3906/sag-1506-125
|View full text |Cite
|
Sign up to set email alerts
|

Colistin efficacy in the treatment of multidrug-resistant and extremelydrug-resistant gram-negative bacterial infections*

Abstract: IntroductionThe polymyxin group of polypeptide antibiotics is among the first antibiotics, discovered in the 1940s, with significant activity against gram-negative bacteria. Both polymyxin E (colistin) and polymyxin B were used clinically. Following reports on nephrotoxicity and neurotoxicity in the 1970s, other antibiotics were used instead of them. In the last decade, this group was reconsidered as a therapeutic option for multidrug-resistant/extremely drug-resistant gram-negative (MDR/XDR-GN) bacterial infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Addressed infections ranged from pneumonia (n = 10 studies) 716 , blood stream infections (n = 15 studies) 1731 , osteoarticular infections (n = 1 study) 32 , and studies comprising mixed forms of infections (n = 27 studies) 3359 . Two of the included studies were RCTs 36,43 , six case-control studies 7,9,15,17,53,55 and forty-five case series/cohort studies 8,1014,16,1835,3742,4452,54,5659 . The studies included a total of 4514 patients: 41% of patients (n = 1848) were treated with monotherapy, 59% (n = 2666) with combination therapy.
Figure 1Study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Addressed infections ranged from pneumonia (n = 10 studies) 716 , blood stream infections (n = 15 studies) 1731 , osteoarticular infections (n = 1 study) 32 , and studies comprising mixed forms of infections (n = 27 studies) 3359 . Two of the included studies were RCTs 36,43 , six case-control studies 7,9,15,17,53,55 and forty-five case series/cohort studies 8,1014,16,1835,3742,4452,54,5659 . The studies included a total of 4514 patients: 41% of patients (n = 1848) were treated with monotherapy, 59% (n = 2666) with combination therapy.
Figure 1Study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…The increased resistance to multiple antibiotics in Gram-negative bacteria presents significant global health-care problems because these MDR Gram-negative pathogens are often not controlled by the available and effective antibiotics [42][43][44]. The advent of MDR Gram-negative bacteria in recent years has made colistin an effective therapeutic alternative for various infections [45]. Two types of risk factor have been described for nosocomial pneumonia: the patient and factors related to infection prevention.…”
Section: Discussionmentioning
confidence: 99%
“…studies reported recovery rates after AKI during polymyxin treatment; these varied widely, ranging from 12% to 100%. Eleven of 46 studies reported recovery in more than 90% patients [38,57,96,136,152,200,204,223,225,228,244], 17 of 46 studies reported recovery rates of 50e90% [7,8,34,48,63,67,68,71,74,84,115,117,183,187,220,222,240] and 18 of 46 studies reported recovery in 50% patients [13,58,67,79,91,104,112,130,148,151,156,162e164, 198,201,208,245]. However, it should be noted that studies differed in the criteria used to define recovery (return to baseline, return to within normal range, no longer meeting criteria for AKI or undefined), the time period of follow-up (end of treatment to 1 year, where given) and the way in which missing data were handled.…”
Section: Nephrotoxicitymentioning
confidence: 99%